Finite Element Algorithm for Dynamic Thermoelasticity Coupling Problems and Application to Transient Response of Structure with Strong Aerothermodynamic Environment (Communications in Computational Physics, 2018)
As an exploratory study for structural deformation and thermodynamic responseinduced by spacecraft reentry aerodynamic force and thermal environment, afinite element algorithm is presented on the basis of the classic Fourier heat conductivelaw to simulate the dynamic thermoelasticity coupling performance of the material.The Newmark method and Crank-Nicolson scheme are utilized to discretizethe dynamic thermoelasticity equation and heat conductive equation in the time domain,respectively, and the unconditionally stable implicit algorithm is constructed.Four types of finite-element computing schemes are devised and discussed to solvethe thermodynamic coupling equation, all of which are implemented and comparedin the computational examples including the one-dimensional transient heat conductionin considering and not considering the vibration, the transient heat flow for theinfinite cylinder, and the dynamic coupling thermoelasticity around re-entry flat platefrom hypersonic aerothermodynamic environment. The computational results showthat the transient responses of temperature and displacement field generate lag phenomenonin case of considering the deformation effect on temperature field. Propagation,rebounding, attenuation and stabilized phenomena of elastic wave are alsoobserved by the finite-element calculation of thermodynamic coupling problem consideringvibration and damping, and the oscillation of the temperature field is simultaneouslyinduced. As a result, the computational method and its application researchplatform have been founded to solve the transient thermodynamic coupling responseproblem of the structure in strong aerodynamic heating and force environment. Bycomparing various coupling calculations, it is demonstrated that the present algorithmcould give a correct and reliable description of transient thermodynamic responses of structure, the rationality of the sequentially coupling method in engineering calculationis discussed, and the bending deformation mechanism produced by the thermodynamiccoupling response from windward and leeward sides of flying body isrevealed, which lays the foundation in developing the numerical method to solve materialinternal temperature distribution, structural deformation, and thermal damageinduced by spacecraft dynamic thermoelasticity coupling response under uncontrolledreentry aerothermodynamic condition.